Frosted branch angiitis as an immune recovery response in newly diagnosed acquired immunodeficiency syndrome and systemic cytomegalovirus infection - Elisa Huynh; Argyrios Chronopoulos; James Scott Schutz; Bernd Claus; Marwa Erwemi; Hermann Krastel; Lars‐Olof Hattenbach (Clinical Case Reports, 2023)
Abstract Frosted branch angiitis (FBA) is an uncommon form of severe retinal perivasculitis associated with systemic inflammatory/infectious diseases. In this report, we describe a case of FBA and macular edema as a result of immune recovery response in a patient newly diagnosed with HIV infection and cytomegalovirus viremia.